Characterisation of PM10 emissions from woodstove combustion of common woods grown in Portugal - Gonçalves, Cátia; Alves, Célia; Evtyugina, Margarita; Mirante, Fátima; Pio, Casimiro; Caseiro, Alexandre; Schmidl, Christoph; Bauer, Heidi; Carvalho, Fernando (Atmospheric Environment, 2010)
A series of source tests was performed to evaluate the chemical composition of particle emissions from the woodstove combustion of four prevalent Portuguese species of woods: Pinus pinaster (maritime pine), Eucalyptus globulus (eucalyptus), Quercus suber (cork oak) and Acacia longifolia (golden wattle). Analyses included water-soluble ions, metals, radionuclides, organic and elemental carbon (OC and EC), humic-like substances (HULIS), cellulose and approximately l80 organic compounds. Particle (PM10) emission factors from eucalyptus and oak were higher than those from pine and acacia. The carbonaceous matter represented 44e63% of the particulate mass emitted during the combustion process, regardless of species burned. The major organic components of smoke particles, for all the wood species studied, with the exception of the golden wattle (0.07e1.9% w/w), were anhydrosugars (0.2e17% w/w). Conﬂicting with what was expected, only small amounts of cellulose were found in wood smoke. As for HULIS, average particle mass concentrations ranged from 1.5% to 3.0%. The golden wattle wood smoke presented much higher concentrations of ions and metal species than the emissions from the other wood types. The results of the analysis of radionuclides revealed that the 226 Ra was the naturally occurring radionuclide more enriched in PM10. The chromatographically resolved organics included n-alkanes, nalkenes, PAH, oxygenated PAH, n-alkanals, ketones, n-alkanols, terpenoids, triterpenoids, phenolic compounds, phytosterols, alcohols, n-alkanoic acids, n-di-acids, unsaturated acids and alkyl ester acids.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Biomass burning; Emissions; GC-MS; Organic tracers; PM10; Woodstove

Volatile and carbohydrate composition of rare unifloral honeys from Spain - Delafuente, E.; Sanz, M.; Martinezcastro, I.; Sanz, J.; Ruizmatute, A. (Food Chemistry, 2007)
Volatile composition and carbohydrate content of Spanish honey samples from uncommon botanical origins have been studied by gas chromatography coupled to mass spectrometry. About 100 volatile compounds were identiﬁed; some of them appeared to be characteristic of particular honey types, such as methyl salycilate in willow (Salix spp.), 2,6,6-trimethyl-2,4-cycloheptadien-1-one (eucarvone) in almond tree (Prunus dulcis) and isophorone in strawberry-tree (Arbutus unedo). Concentration ranges for major carbohydrates were similar to those previously reported in other honeys with diﬀerent botanical origins, although concentrations of maltulose in avocado honeys (Persea americana) and of melezitose in Quercus ilex honeys were higher. Some carbohydrate alcohols could also be considered as markers of honey botanical origin, such as quercitol for Q. ilex and perseitol for avocado.
Keywords: carbohydrates; gc; GC-MS; honey; ms; polyalcohols; volatile compounds

Effect of exogenous ABA on embryo maturation and quantification of endogenous levels of ABA and IAA in Quercus suber somatic embryos - GARCÍA-MARTÍN, G (Plant cell, tissue and …, 2005)
Knowledge of the relationship between indole-3-acetic acid (IAA) and abscisic acid (ABA) is relevant to control the development and the maturation of cork oak (Quercus suber L.) somatic embryos. The addition of 1 lM ABA to the culture medium signiﬁcantly promoted somatic embryo maturation and increased both fresh and dry matter without aﬀecting the relative water content. This eﬀect was parallel to the pattern of variation observed in the endogenous ABA level, which increased from the immature to the mature stage. Endogenous ABA content during the occurrence of secondary embryogenesis was similar to that of the immature stage, showing that embryos with lower ABA levels produced secondary embryos. In contrast, IAA showed the highest concentration during early embryo development and decreased afterwards. Only in somatic embryos subjected to 1-week desiccation followed by stratiﬁcation at 4 C for 2 weeks, was a moderate increment of endogenous IAA content observed. IAA and ABA showed opposite levels during the development and maturation of cork oak somatic embryos and characterised speciﬁc stages of the embryonic development.
Keywords: Cork oak; endogenous plant growth regulators; GC-MS; hplc; in vitro; somatic embryo

Effect of exogenous ABA on embryo maturation and quantification of endogenous levels of ABA and IAA in Quercus suber somatic embryos - Garcia-Martin, G. (Plant cell, tissue and …, 2005)
Knowledge of the relationship between indole-3-acetic acid (IAA) and abscisic acid (ABA) is relevant to control the development and the maturation of cork oak (Quercus suber L.) somatic embryos. The addition of 1 lM ABA to the culture medium signiﬁcantly promoted somatic embryo maturation and increased both fresh and dry matter without aﬀecting the relative water content. This eﬀect was parallel to the pattern of variation observed in the endogenous ABA level, which increased from the immature to the mature stage. Endogenous ABA content during the occurrence of secondary embryogenesis was similar to that of the immature stage, showing that embryos with lower ABA levels produced secondary embryos. In contrast, IAA showed the highest concentration during early embryo development and decreased afterwards. Only in somatic embryos subjected to 1-week desiccation followed by stratiﬁcation at 4 C for 2 weeks, was a moderate increment of endogenous IAA content observed. IAA and ABA showed opposite levels during the development and maturation of cork oak somatic embryos and characterised speciﬁc stages of the embryonic development.
Keywords: Cork oak; endogenous plant growth regulators; GC-MS; hplc; in vitro; somatic embryo

Composition of Suberin Extracted upon Gradual Alkaline Methanolysis of Quercus suber L. Cork - Lopes, Marta H.; Gil, Ana M.; Silvestre, Armando J. D.; Neto, Carlos Pascoal (Journal of Agricultural and Food Chemistry, 2000)
The monomeric composition of suberin extracts obtained by gradual alkaline methanolysis of Quercus suber cork was determined by gas chromatography?mass spectrometry (GC-MS). Results show that 1-alkanols and alkanoic and α,?-alkanedioic acids are preferentially removed upon mild alkaline conditions, whereas mid-chain-modified ?-hydroxyalkanoic acids are preferentially removed under stronger alkaline conditions. Saturated ?-hydroxyalkanoic acids are found to be abundant in all suberin extracts. These results are consistent with two distinct suberin fractions with different locations in cork cell walls and/or esterification degrees. It is proposed that these fractions correlate with the two main suberin peaks in the solid state 13C NMR spectra of cork and suberin extracts. Quantitative GC-MS analysis showed that suberin monomers comprise ?30% (w/w) of the suberin extracts, the remaining comprising nonvolatile structures with high Mn values, as measured by vapor pressure osmometry. The presence of a large fraction of high molecular weight aliphatic structures in suberin extracts is supported by the corresponding NMR spectra. Keywords: Suberin; cork; Quercus suber L.; GC-MS; NMR; alkaline methanolysis
doi: 10.1021/jf9909398doi: 10.1021/jf9909398The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Alkaline methanolysis; Cork; GC-MS; NMR; Quercus suber L.; suberin

Quantitative Assessment of Polycyclic Aromatic Hydrocarbons from Corkwaste Combustion Emissions - Cabañas, Aracel; Sáez, Felicia; González, Alberto; Escalada, Ricardo (Journal of Agricultural Engineering Research, 2000)
Cork is a natural raw material obtained from the cork oak (Quercus suber). The corkwaste is a potential source of polycyclic aromatic hydrocarbons (PAHs) due to its high content of volatile compounds. A sampling method was developed for the measurement of polycyclic aromatic hydrocarbons emissions in a pilot bubbling #uidized bed combustion. This method has been designed to assess simultaneously the PAH contained in the gas phase and in the particulate matter. The samples were analysed on a gas chromatography coupled to a mass spectrometer to identify and quantify PAH compounds. The mass-selective detector was run in the selected ion monitoring mode. This study shows that lower molecular weight PAH were present predominantly in the gas phase, whereas high weight PAHs were retained in the particulate phase. As there is an existing relationship between the emission of CO and polycyclic aromatic hydrocarbons, the control and assessment of both compounds have been performed.
Keywords: Cork waste; Fluidized bed combustion (PG); GC-MS; Polycyclic aromatic hydrocarbons (PAHs)

Quantitative Assessment of Polycyclic Aromatic Hydrocarbons from Corkwaste Combustion Emissions - Cabañas, Aracel; Sáez, Felicia; González, Alberto; Escalada, Ricardo (Journal of Agricultural Engineering Research, 2000)
Cork is a natural raw material obtained from the cork oak (Quercus suber). The corkwaste is a potential source of polycyclic aromatic hydrocarbons (PAHs) due to its high content of volatile compounds. A sampling method was developed for the measurement of polycyclic aromatic hydrocarbons emissions in a pilot bubbling #uidized bed combustion. This method has been designed to assess simultaneously the PAH contained in the gas phase and in the particulate matter. The samples were analysed on a gas chromatography coupled to a mass spectrometer to identify and quantify PAH compounds. The mass-selective detector was run in the selected ion monitoring mode. This study shows that lower molecular weight PAH were present predominantly in the gas phase, whereas high weight PAHs were retained in the particulate phase. As there is an existing relationship between the emission of CO and polycyclic aromatic hydrocarbons, the control and assessment of both compounds have been performed.
Keywords: Cork waste; Fluidized bed combustion (PG); GC-MS; Polycyclic aromatic hydrocarbons (PAHs)

Signatures of lipid assemblages in soils under continental Mediterranean forests - Almendros, G; Sanz, J; VELASCO, F (European Journal of Soil Science, 1996)
The analysis of free lipids in 12 soils from three representative types of Mediterranean forest has been carried out in an attempt to describe diagnostic molecules reflecting differences between the ecosystems and the intensity of the soil organic matter turnover. The study centred on the analysis by gas chromatography–mass spectrometry of the soil compounds extracted with petroleum ether from soils in central Spain, developed under monospecific formations of stone pine (Pinus pined), evergreen oak (Quercus rotundifolia) and Spanish juniper (Juniperus thurifera), the lipid extracts from their leaves also being analysed as reference material. The comparison between the distribution patterns of alkanes and fatty acids in plant lipids and the corresponding soil lipids was used to assess the extent to which the former accumulate in soil or are substituted by other biogenic or diagenetic homologues. In general, the alkane patterns showed the greatest variation in soils under oak, and the differences between lipid patterns in plant and soil were greatest in the juniper forests. As indicators of the vegetation type, the soil fatty acids had little value. Up to 60 major cyclic compounds were identified, including mainly di- and sesquiterpenes, in addition to some monoterpenes and nonterpenic naphthalenes and decalins. Of these major constituents, 33 compounds were found in soil but were not present in plant extracts, and 18 compounds were identified in plants but were not in the soils. The results suggest an arrangement of the soil samples based on the composition of the signature lipid assemblages.
Keywords: GC-MS; Lipids; Lipids assemblage (voyant); mediterranean forest soils

Signatures of lipid assemblages in soils under continental Mediterranean forests - ALMENDROS, G.; Sanz, J.; VELASCO, F. (European Journal of Soil Science, 1996)
The analysis of free lipids in 12 soils from three representative types of Mediterranean forest has been carried out in an attempt to describe diagnostic molecules reflecting differences between the ecosystems and the intensity of the soil organic matter turnover. The study centred on the analysis by gas chromatography–mass spectrometry of the soil compounds extracted with petroleum ether from soils in central Spain, developed under monospecific formations of stone pine (Pinus pined), evergreen oak (Quercus rotundifolia) and Spanish juniper (Juniperus thurifera), the lipid extracts from their leaves also being analysed as reference material. The comparison between the distribution patterns of alkanes and fatty acids in plant lipids and the corresponding soil lipids was used to assess the extent to which the former accumulate in soil or are substituted by other biogenic or diagenetic homologues. In general, the alkane patterns showed the greatest variation in soils under oak, and the differences between lipid patterns in plant and soil were greatest in the juniper forests. As indicators of the vegetation type, the soil fatty acids had little value. Up to 60 major cyclic compounds were identified, including mainly di- and sesquiterpenes, in addition to some monoterpenes and nonterpenic naphthalenes and decalins. Of these major constituents, 33 compounds were found in soil but were not present in plant extracts, and 18 compounds were identified in plants but were not in the soils. The results suggest an arrangement of the soil samples based on the composition of the signature lipid assemblages.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: GC-MS; Lipids; Lipids assemblage (voyant); mediterranean forest soils